THE EFFECTS OF MALOLACTIC FERMENTATION AND BENTONITE TREATMENT ON THE AROMA OF WINES FROM AUTOCHTHONOUS KRSTAČ AND ŽIŽAK VARIETIES - Madžgalj, Valerija; Živković, Nikolina; Sofrenić, Ivana; Tešević, Vele; Petrović, Aleksandar (Food and Feed Research, 2024)
Abstract: The aim of this study was to investigate the influence of two lactic acid bacteria strains (Lactobacillus plantarum, Oenococcus oeni) and a bentonite treatment on the content of aromatic compounds in wines of the autochthonous grape varieties Krstač and Žižak. Higher alcohols, medium-chain fatty acids (C6, C8, C10), esters and other volatile compounds were detected by GC/FID-MS analysis. The concentration of higher alcohols was lower in the wines from Krstač and Žižak in which malolactic fermentation was performed. The results of this study showed that the content of aromatic compounds depends on the lactic acid bacterial strains. L. plantarum yielded a higher content of total higher alcohols and esters compared to O.oeni. The content of total esters ranged from 30.28 to 32.70 mg/L for Krstač wines and from 19.35 to 23.21 mg/L for Žižak wines. O. oeni and L. plantarum had a statistically significant effect on the concentration of most esters. Lactic acid bacteria significantly reduced the content of ethyl butyrate, ethyl hexanoate, ethyl decanoate and isoamyl acetate. Furthermore, the content of ethyl lactate, diethyl hydroxybutanedioate, diethyl succinate and ethyl hidrogen succinate was higher in wines produced with L. plantarum. The addition of bentonite in increasing concentrations did not affect the concentration of the higher alcohols in Žižak wines. The lowest content of fatty acids was detected in wines produced with  200 g/hL bentonite.